Diálogos da obra e do acervo de Fernando Sabino com a cultura literária de língua inglesa - Cristina Gonçalves Ferreira de Souza (2024)
This thesis analyzes the dialogues between the work and collection of the writer Fernando Sabino and the literary culture of the English language, with the aim of understanding the importance of this relationship for the construction of his literature. The hypothesis defended is that the relationship of the writer with the literary culture of the English language is significant for the constitution of the history of his work and that reflections of this relationship could be found in his books and collection. Supported by theories and using the method of biographical criticism, I present, in the first chapter, the biobibliography of the writer, which outlines his relationship with the literary culture of the English language from childhood to adulthood; I analyze, in the second chapter, works written during the period in which he lived in the United States and subsequent years in which he dialogues with English-speaking writers; in the third chapter, I analyze works by English-speaking writers present in his literary collection with which he establishes explicit literary dialogues in marginalia and quotations; and finally, in the conclusion, I address the cosmopolitanism in Sabino's life and work, in order to suggest a classification for his work through this bias, which explains and, at the same time, justifies his relationship with the English-language literary culture. As a result, I found strong evidence of the relationship of the writer and his work with the English-language literary culture that proves the importance of this culture for his literature.